Peripheral insulin and amylin levels in Parkinson's disease. (October 2020) - Sánchez-Gómez, Almudena; Alcarraz-Vizán, Gema; Fernández, Manel; Fernández-Santiago, Rubén; Ezquerra, Mario; Cámara, Ana; Serrano, Mònica; Novials, Anna; Muñoz, Esteban; Valldeoriola, Francesc; Compta, Yaroslau; Martí, Maria José
Abstract: Background: Type-2-diabetes (T2D) has surfaced as a potential risk factor for Parkinson's disease (PD) in some epidemiological studies. Evidence of glucose metabolism alterations in PD from molecular studies remains conflicting. Amylin, the T2D amyloid protein, has been implicated in PD in pathological studies. We aimed to assess peripheral levels of amylin and insulin in PD patients and control subjects (Cs). Methods: We conducted an observational cross-sectional study of 111 participants: 73 PD and 38 Cs, similar in age, sex and body mass index. All underwent motor (UPDRS-MDS-III), non-motor (NMSS) and cognitive (MDRS) scales as well as determination of four parameters: fasting glycaemia, glycated haemoglobin, fasting plasma insulin (FPI) and fasting plasma amylin (FPA). Results: FPI was significantly lower in PD than Cs (p = 0.034). In participants with age above cohort-median-age, FPA was higher in PD than Cs (p = 0.046). The FPA/FPI ratio (FPAIR) was significantly higher in PD than Cs (p = 0.024). In PD, modest correlation was found between higher insulin-resistance and NMSS scores. Conclusions: PD patients had lower FPI and increased FPAIR. In older PD subgroup, FPA was increased. The more the insulin resistance, the higher the non-motor scores. These findings provide an additional link between pathophysiology of diabetes and PD. This might be related to a dissociated insulin and amylin secretion in PD, in line with recent evidence of endocrine pancreas role in PD pathogeny. Highlights: Parkinson's disease (PD) patients had lower insulin levels than healthy controls. Plasma amylin was higher in older PD patients and plasma amylin/insulin ratio was higher too in PD. Higher values of HOMA-IR (insulin resistance) were related to increased non-motor symptoms scores (NMSS).